FREKUENSI KUNJUNGAN ANTENATAL CARE (ANC) IBU HAMIL DI PKD KERTASARI KECAMATAN KALIBENING KABUPATEN BANJARNEGARA TAHUN 2010 - Ari Tri Sulistyaningsih; Prasanti Adriani (Viva Medika, 2011)
Mortality Ms. ( AKI) And Mortality Baby ( AKB) in Indonesia pertained still highenough. One of the effort degradation of ACCUMULATOR and AKB is Antenatal visit of Care ( Ministry of Health, 2011). Pursuant to done/conducted by survey pre data in PKD Kertasari inthe year 2009 to 54 pregnant mother and only 47 ( 87%) pregnant mother execute Antenatal visitof Care. Knowing Antenatal visit frequency of Care at pregnant mother in PKD Kertasari, Districtof Kalibening, Sub-Province Banjarnegara Year 2010. Research type is quantitative descriptive, with approach of retrospektif. Its populationentire/all pregnant mother in PKD Kertasari, District of Kalibening, Sub-ProvinceBanjarnegara Year 2010. its Intake technique of nya use total technique of sampling that isentire/all pregnant mother which reside in region in PKD Kertasari. Ms. pregnancy doing/conducting Antenatal visit of Care counted 62%. Pursuant topregnant mother age which do/conduct Antenatally of Biggest Care that is at age 20 until 35year, pursuant to parity that is at nullipara group that is 78%. Antenatal Visit K4 frequency of pregnant Care Mother in new PKD Kertasari 62 %, sothat still require to be improved Keyword : frequency, Antenatal of Pregnant Care,Ibu